PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK PADA TEMATIK MUATAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS IV SD SOKOWATEN BARU - Desty Sinta Anggraini; Kristi Wardani (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to find out (1) developing a thematic Worksheet (LKPD) for PPKn content for grade IV elementary school, (2) knowing the feasibility of learning products made. This research includes development research. The data collection techniques used were observation and documentation. The data analysis techniques used was qualitative data analysis and quantitative data analysis. The results showed that LKPD products were suitable for use. LKPD teaching materials obtain a feasibility percentage from material experts 83.5% with very feasible criteria, the results of the feasibility percentage from thematic experts 91.3% with very feasible criteria, the results of the feasibility percentage of class teachers 86% with criteria very feasible, and the results of feasibility percentage from the principal 84.5% with very decent criteria. The response of students from small-scale trials obtained a percentage of 90.13% with very feasible criteria, while a large scale obtained an average score of 80.5 with very good criteria. The conclusion is that the Student Worksheet (LKPD) in Thematic Contents of Pancasila and Civic Education in Class IV of Sokowaten Baru Elementary School in Yogyakarta Academic Year 2018/2019 is very feasible to use as teaching material and learning.